DETERMINING FACTORS FOR THE SELECTION OF SHARIA BANK - Setiyaningsih, Rozi Fery; Pramuka, Bambang Agus (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study examines the determinants of the community selection of Islamic banks. Specifically, this study aims to determine how the influence of Islamic financial literacy and service quality on the selection of Islamic banking is mediated by trust. Islamic banking is increasingly needed as a transaction medium along with an increasing number of Indonesian halal industries. Islamic banking is rapidly growing, but it has a low market share, reaching only 6.59% of Indonesia's population in July 2021. This study uses the SmartPLS 3 tool with the Partial Least Squares (PLS) analysis method. Respondents in this study were 163 respondents, namely customers of Islamic banks from the Pekalongan ex-residency. The results show that Islamic financial literacy does not affect the selection of Islamic banks, which is interesting because it turns out that Islamic financial literacy will affect the selection of Islamic banks if mediated by trust. Service quality has a significant positive effect on the selection of Islamic banks, and service quality affects the selection of Islamic banks mediated by trust. Trust affects the selection of Islamic banks. This research implies that customers need to improve Islamic financial literacy in forming trust in Islamic bank products and services. In addition, the need to improve the quality of service. Building customer trust requires a high sense of awareness and intention.